Transformation of Zakat Into Rotating Business Capital: A Sustainable Economic Empowerment Solution - Hana Mabrukah; Anwar Ibrahim Sadiq (JOURNAL OF ISLAMIC ECONOMICS AND BUSSINES ETHICS, 2024)
Zakat one of the important pillars of Islam, has great potential to empower the economic status of Muslims. Traditional distribution of zakat often fails to produce long-term economic improvement for its recipients. The current zakat problems are very complex, starting from the fact that there are still some people who do not want to pay zakat, the distribution of zakat that has not been arranged properly to the problem of fiqh regarding the development and ijtihad for productive zakat models. Productive zakat is making zakat money not only consumptive in the sense that it is immediately consumed, but zakat assets are used for business capital to eradicate poverty for zakat recipients. With this business capital, it is hoped that zakat recipients will one day become muzakki. This study aims to investigate the transformation of zakat into revolving business capital and its impact on the economic empowerment and self-reliance of mustahik (zakat recipients). The hypothesis tested is that zakat, when used as revolving business capital, can significantly improve the economic welfare of mustahik. This research uses a qualitative approach with a literature review methodology. Data was sourced from various secondary materials including scientific articles, institutional reports, and case studies of successful zakat programs. Data analysis involved thematic analysis to identify key factors that contribute to the success and challenges of zakat-based revolving business capital programs. The findings show that a well-managed revolving business capital program significantly improves the income and welfare of mustahik. Key success factors include ongoing business training and support, continuous monitoring and evaluation, and transparent fund management. Partnerships with government entities, the private sector, and local communities also enhance program effectiveness. Statistical analysis shows a positive correlation between participation in the program and increased economic independence of mustahik. The transformation of zakat into revolving business capital is an effective solution for sustainable economic empowerment. Proper management and strategic partnerships are critical to the success of this program, which not only reduces poverty but also encourages the economic independence of mustahik.